Demographics, social media use and perceived academic stress of secondary school students in St. Thomas Aquinas College, Akure, Nigeria - Igbinovia, Magnus Osahon; Idhalama, Ogagaoghene Uzezi; Alex-Nmecha, Juliet C (International Journal of Knowledge Content Development & Technology, 2019)
The study was carried out to investigate the influence of demographics and social media use on perceived academic stress of secondary school students in St. Thomas Aquinas College, Akure, Nigeria. This was achieved using five research questions and four null hypotheses. The population of the study consisted of 1,107 students at ISCED level 3, out of which 286 were selected based on the Israel (2003) model for determining sample size. The Ex-Post Facto (EPT) research design of the correlational type was employed to investigate the study while questionnaire was used for data elicitation. Out of the 286 copies distributed, 192 (67% response rate) were retrieved and analysed using descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistics (correlation and multiple regression). The findings revealed that there is high frequency of social media use among secondary school students, majorly for meeting new friends and chatting. The perceived academic stress (PAS) of the students was found to be moderate. Of the three demographics considered, only class had significant influence on PAS. Use of social media did not have significantly influence on PAS of the students. When combined, demographics and social media use predicted PAS; and when considered relatively, of the independent variables, only class as an aspect of demographics predicted PAS. Therefore, the authors concluded that PAS of secondary school students is not directly influenced by demographics (except for class) and social media use. Based on the study’s conclusion, recommendations were made. URL: http://ijkcdt.net/xml/22142/22142.pdf